2019
DOI: 10.1007/s00213-019-05366-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled, phase 1 study to evaluate the effects of TAK-063 on ketamine-induced changes in fMRI BOLD signal in healthy subjects

Abstract: Rationale Phosphodiesterase 10A inhibitor TAK-063 has shown effects that suggest efficacy in schizophrenia treatment. Objective This randomized, double-blind, placebo-controlled, incomplete-crossover study investigated effects of single oral administration of TAK-063 on ketamine-induced changes in blood oxygen level-dependent (BOLD) signal in healthy males. Methods Healthy men aged 18 to 45 years with normal magnetic resonance imaging (MRI) scans and electroencephalogram measurements at screening were eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…To extend the phMRI findings in rodents, TAK-063 was investigated in ketamine-treated healthy human subjects ( Yurgelun-Todd et al, 2020 ). Compared with placebo, TAK-063 reduced ketamine-induced increases in BOLD signal across all brain regions analyzed during the working memory task ( Figure 2 ; Supplementary Figure S3 ) in a dose-dependent manner ( Yurgelun-Todd et al, 2020 ). The most consistent reversal of ketamine-induced effects in fMRI was observed in the 30-mg TAK-063 dose group, which approximates the steady state exposure of 20 mg ( Macek et al, 2016b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To extend the phMRI findings in rodents, TAK-063 was investigated in ketamine-treated healthy human subjects ( Yurgelun-Todd et al, 2020 ). Compared with placebo, TAK-063 reduced ketamine-induced increases in BOLD signal across all brain regions analyzed during the working memory task ( Figure 2 ; Supplementary Figure S3 ) in a dose-dependent manner ( Yurgelun-Todd et al, 2020 ). The most consistent reversal of ketamine-induced effects in fMRI was observed in the 30-mg TAK-063 dose group, which approximates the steady state exposure of 20 mg ( Macek et al, 2016b ).…”
Section: Resultsmentioning
confidence: 99%
“…EEG studies were also conducted in subjects with stable schizophrenia (SSS) who were on stable antipsychotic monotherapy and received 3, 10, 30, or 100 mg TAK-063 during a 7-day multiple-rising dose study ( Macek et al, 2016a ); according to Goldsmith et al ( 2017 ), SSS can be defined as an individual on stable antipsychotic monotherapy for ≥1 month before screening, who had a Clinical Global Impression of Severity score ≤4, and a total Positive and Negative Symptom Scale score ≤70 at screening and check-in (Day -1; Macek et al, 2016a ; Goldsmith et al 2017 ). Additionally, an EEG was assessed in healthy subjects who received 3, 10, and 30 mg TAK-063 in an incomplete crossover, ketamine-challenge, functional MRI (fMRI) study ( Yurgelun-Todd et al, 2020 ); ClinicalTrials.gov ID: NCT01892189), and EEG recordings were made after the imaging battery was complete, which was approximately 5 hours after the administration of study medication (n = 14 for 3 mg and 10 mg doses; n = 15 for 30 mg dose). In the multiple-rising dose study, 10-minute samples of 19-channel EEG recordings were taken while subjects were either (1) seated with eyes closed (resting condition) or (2) presented with high-frequency auditory stimuli at 40 Hz in blocks (40-Hz condition; n = 9 for placebo; n = 7 for 100 mg dose).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its blockage in animal models of schizophrenia using rodents and apes induces a beneficial effect in cognitive deficit [ 217 , 218 ]. TAK-063, a PDE10 inhibitor, has reached clinical trials, and although it was shown to be safe in phase 1 [ 219 ], it did not show a significant improvement in cognitive abilities in phase 2 studies with schizophrenic patients [ 119 ].…”
Section: Treatment Of Cognitive Deficit In Schizophreniamentioning
confidence: 99%
“…TAK-063 [1-[2-uoro-4-(1H-pyrazol-1-yl)phenyl]-5-methoxy-3-(1-phenyl-1H-pyrazol-5-yl)pyridazin-4(1H)-one] is a potent and highly selective inhibitor of PDE10A [13]. Preclinical and clinical data indicate that TAK-063 is safe and well tolerated in humans [14,15]. Harada et.…”
Section: Introductionmentioning
confidence: 99%